2013
DOI: 10.1186/1756-0500-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear stress and substrate on endothelial DAPK expression, caspase activity, and apoptosis

Abstract: BackgroundIn the vasculature, misdirected apoptosis in endothelial cells leads to pathological conditions such as inflammation. Along with biochemical and molecular signals, the hemodynamic forces that the cells experience are also important regulators of endothelial functions such as proliferation and apoptosis. Laminar shear stress inhibits apoptosis induced by serum depletion, oxidative stress, and tumor necrosis factor α (TNFα). Death associated protein kinase (DAPK) is a positive regulator of TNFα induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…17 Altering the flow shear stress and wall stress in the arterial wall are well known to stimulate vascular cell functions, including cell proliferation and apoptosis. 12, 21, 34, 36 Our simulation demonstrated significant changes in wall stresses in buckled arteries post-grafting, especially in axial stress (Fig. 8c).…”
Section: Discussionmentioning
confidence: 71%
“…17 Altering the flow shear stress and wall stress in the arterial wall are well known to stimulate vascular cell functions, including cell proliferation and apoptosis. 12, 21, 34, 36 Our simulation demonstrated significant changes in wall stresses in buckled arteries post-grafting, especially in axial stress (Fig. 8c).…”
Section: Discussionmentioning
confidence: 71%
“…DAPK is upstream of the caspases, with the exception of caspase 8, and may induce caspase-independent cell death or autophagy. Previous studies have determined that DAPK contributed to shear stress-induced endothelial apoptosis (20,21). However, the importance of DAPK in Hcy-induced apoptosis in endothelial cells remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have cultured vascular cells on 3D collagen scaffolds within their flow chambers to more accurately reproduce the in vivo substrate conditions [32,36]. Rennier and Ji found similar EC response to steady FSS (as indicated by DAPK expression and apoptosis) regardless of whether the cells were cultured on glass or silicone [28]. However, that does not rule out the potential importance of substrate stiffness on cell response.…”
Section: Introductionmentioning
confidence: 93%
“…In the past, most parallel-plate flow chambers have used glass or rigid glasslike materials as a substrate for cell culture [13,18,33,34]. For cells to attach to a rigid substrate, researchers must coat the substrate with fibronectin, collagen, or gelatin [12,18,28,35], or allow the cells time to lay down their own matrix [13]. Rennier and Ji demonstrated that fibronectin-coated silicone membranes (similar to those used for Fig.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation